Application of the concept of tancegrity in the rehabilitation of children with intellectual disabilities - Fedulova D.V.; Berdyugin K.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify postural disorders in children with mental retardation and to develop a method of physical rehabilitation based on the positions of the tansegrity model. Methods and structure of the study. The scientific work involved 80 children born in 2008-2009, evenly distributed into 2 groups: with mild mental retardation and healthy schoolchildren. It was proposed to use three tests: scoliometry, measurement of flexibility in forward bending and a test of visual assessment of functional shortening of muscles and muscle imbalance, to determine existing disorders according to the theory of myofascial chains of T. Myers and the concept of the tansegrity model. Results and conclusions. Rehabilitation training, developed using the TRX system to correct identified disorders, showed positive results and the effectiveness of the physical rehabilitation technique. In particular, scoliometry indicators improved in 25% of children with mental retardation, flexibility increased by 5.39 cm (before the experiment -5.14±2.01, after two courses of rehabilitation 0.25±1.82), functional shortening of muscles in the form of lateral deviation corresponded to scoliometry data: when compared with the initial data, in 25% of children after the experiment there was no movement of the body beyond the midline when bending forward.